ChemInform Abstract: A Diversity‐Oriented Synthesis of Caroverine Derivatives via TEMPO‐Promoted Aerobic Oxidative C—N Bond Formation. Issue 46 (18th November 2014) - Kobayashi, Yusuke; Suzuki, Yusuke; Ogata, Tokutaro; Kimachi, Tetsutaro; Takemoto, Yoshiji
Abstract The synthesis of caroverine derivatives is based on a tandem nitrosation/aerobic C‐N bond formation reaction of substrate (I).